Diet Control More Intensively Disturbs Gut Microbiota Than Genetic Background in Wild Type and ob/ob Mice - Wang, Jing-Hua; Shin, Na Rae; Lim, Soo-Kyoung; Im, Ungjin; Song, Eun-Ji; Nam, Young-Do; Kim, Hojun (Frontiers in Microbiology, 2019)
Changes in environmental and genetic factors are vital to development of obesity and its complications. Induction of obesity and type 2 diabetes by both leptin deficiency (ob/ob) and high fat diet (HFD) has been verified in animal models. In the present experiment, three types of diets (normal diet; ND, HFD and high sucrose diet; HSD) and two types of genetic mice (Wild type: WT and ob/ob) were used to explore the relationship among diet supplements, gut microbiota, host genetics and metabolic status. High fat diet increased the body, fat and liver weight of both ob/ob and WT mice, but HSD did not. High fat diet also resulted in dyslipidemia, as well as increased serum transaminases and fasting glucose in ob/ob mice but not in WT mice, while HSD did not. Moreover, HFD led to brain BDNF elevation in WT mice and reduction in ob/ob mice, whereas HSD did not. Both HFD and HSD had a greater influence on gut microbiota than host genotypes. In detail, both of HFD and HSD alteration elucidated the majority (≥ 63%) of the whole structural variation in gut microbiota, however, host genetic mutation accounted for the minority (≤ 11%). Overall, diets more intensively disturbed the structure of gut microbiota in excess of genetic change, particularly under leptin deficient conditions. Different responses of host genotypes may contribute to the development of metabolic disorder phenotypes linked with gut microbiota alterations.